ANALISIS KERAGAMANGENETIK DNA UBI JALAR (Ipomea batatas L.)DENGAN MARKA RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) - Wulan Dari, Tri; Idami, Zahratul; Manalu, Kartika (Jurnal Biogenerasi, 2026)
Sweet potato (Ipomea batatas L.) is a national food security supported by one of the potential plant resources. After rice, corn, and cassava, sweet potato (Ipomea batatas L.) contains the fourth highest carbohydrate. Sweet potato is a good source of thiamine (vitamin B1), riboflavin, vitamin A, vitamin B, and vitamin C. The purpose of this study was to determine the genetics of the analysis results presented in sweet potato (Ipomea batatas L.) using dendograms and DNA banding patterns in sweet potatoes based on RAPD markers. The research method used is an experimental method to collect data by conducting direct experiments, isolating DNA, and conducting PCR using the RAPD technique; Six RAPD primers were used: OPA 2, OPA 3, OPA5, OPA7, OPD 11, and OPD 13. The study resulted in genetic diversity seen from the DNA banding pattern that forms polymorphism. RAPD produces bands measuring 100-900 bp. The genetic diversity of 4 types of Ipomea batatas L. plants analyzed using the NTSYS pc-2.02i application on the kinship relationship displayed with a dendogram shows the same diversity, namely orange sweet potatoes with yellow sweet potatoes, which have the highest level of similarity because they join at a coefficient value of around 0.91. While in purple sweet potatoes joining the group (yellow sweet potatoes and orange sweet potatoes) at a coefficient value of 0.86 indicates that purple sweet potatoes are slightly more different but still in the group. Then in white sweet potatoes have a connection coefficient value of around 0.81 which indicates that this sample is the most different compared to the others)